Nutritional status and pregnancy outcomes between anaemic and non anaemic pregnant women in Hulu Selangor, Malaysia - Zalbahar @ Zabaha, Nurzalinda (2009)
Anaemia among pregnant women has been documented to be associated with low birth weight and poor health status of newborns. Anaemia due to lack of certain nutrients before and during pregnancy remains a great concern worldwide. Chronic nutrient deficiencies during the pregnancy stage will affect not only the health status of the mother but also the infant’s birth weight and general development. A comparative study on nutritional status and pregnancy outcomes between anaemic and non-anaemic pregnant women were done. This study was conducted in the districts of Hulu selnagor, Selangor. A total of 188 pregnant mothers in their third trimesters and fulfilling the inclusion criteria from five health clinics (KK Kuala Kubu Baru, KK Kalumpang, KK Rasa, KK Hulu Yam, and KK Serendah) were recruited and interviewed. A set of questionnaire were used to collect data on socio-demographic background, history of the pregnancy, and other health related data. Dietary intake was assessed using a Semi-Quantities Food Frequency Questionnaire. Pregnancy outcome data and infant nutritional and health data were collected after delivery and after the infant has reached one month of age. All data were analyzed by using SPSS version 16.0 and dietary data with Nutritionist Pro version 2.4.1 was used to analyze subjects’ nutrient intake. Independent t-test was used to compare differences of means between the two groups. Out of 188, 90 were anaemic (A) and 98 were non-anaemic (NA). The mean values for haemoglobin levels for (A) and (NA) subjects were 10.1±0.8g/dl and 11.9±0.7g/dl, respectively. The mean age for anaemic mothers was 29.1±5.0 and that of non-anaemic mothers was 29.1 ± 5.2 years old. Majority of them had secondary level education and ranked at the fourth Social Class level with the range of monthly household income between RM1001-2000. About 40% of the subjects were fulltime housewives. The rest were working in government and private sectors. The mean weight gain was 8.1±4.7kg for (A) and 7.9±4.6 kg for (NA) throughout their pregnancies. Majority of the babies were delivered normally, and 2% of non-anaemic mothers delivered stillbirth infants. Only 13% of the babies were delivered by Caesarean section and 1% by the vacuum method foe anaemic subjects, while 22% were delivered by Caesarean section by non-anaemic subjects. Majority of infants given birth by the subjects had normal birth weights (>2.5kg). The mean birth weight for babies of anaemic subjects was 3.2±0.5 kg, while that of non-anaemic subjects was 3.1±0.5kg. About 39.5% for (A) and 44.9% for (NA) gave birth to preterm babies with a mean of 36 weeks and 32 weeks respectively. After one month of age, both (A) and (NA)’s infants were not significantly different on weight, length, chest circumference and head circumference. In terms of nutrient intake, there were significant differences between (A) and (NA) on carbohydrate (p = 0.001) and calcium (p = 0.049) intakes. Other nutrient intake showed no significant difference between the two groups. MANOVA analysis wre done included confounding factors which also shown significantly indifference on birth weight and term birth of infants between anaemic and non-anaemic subject. Thus the overall results indicated that the nutitional status and pregnancy outcomes between both groups were similar. However, the concern was towards all pregnant women with or without anaemia on understanding and implementing good nutritional status in order to have good pregnancy outcomes. Ongoing research need to be done and focus on those who having more severe anaemia status which has low haemoglobin level of less than 9g/dl.